Phylogenetic conservation of Trop-2 across species—rodent and primate genomics model anti-Trop-2 therapy for pre-clinical benchmarks - Guerra, Emanuela; Trerotola, Marco; Relli, Valeria; Lattanzio, Rossano; Boujnah, Khouloud; Travali, Nicole; Moschella, Antonino; Todaro, Paolo; Pierdomenico, Laura; Di Pietro, Roberta; Tinari, Nicola; Alberti, Saverio (Frontiers in Genetics, 2024)
A phylogenetic conservation analysis of Trop-2 across vertebrate species showed a high degree of sequence conservation, permitting to explore multiple models as pre-clinical benchmarks. Sequence divergence and incomplete conservation of expression patterns were observed in mouse and rat. Primate Trop-2 sequences were found to be 95%–100% identical to the human sequence. Comparative three-dimension primate Trop-2 structures were obtained with AlphaFold and homology modeling. This revealed high structure conservation of Trop-2 (0.66 ProMod3 GMQE, 0.80–0.86 ± 0.05 QMEANDisCo scores), with conservative amino acid changes at variant sites. Primate TACSTD2/TROP2 cDNAs were cloned and transfectants for individual ORF were shown to be efficiently recognized by humanized anti-Trop-2 monoclonal antibodies (Hu2G10, Hu2EF). Immunohistochemistry analysis of Macaca mulatta (rhesus monkey) tissues showed Trop-2 expression patterns that closely followed those in human tissues. This led us to test Trop-2 targeting in vivo in Macaca fascicularis (cynomolgus monkey). Intravenously injected Hu2G10 and Hu2EF were well tolerated from 5 to 10 mg/kg. Neither neurological, respiratory, digestive, urinary symptoms, nor biochemical or hematological toxicities were detected during 28-day observation. Blood serum pharmacokinetic (PK) studies were conducted utilizing anti-idiotypic antibodies in capture-ELISA assays. Hu2G10 (t1/2 = 6.5 days) and Hu2EF (t1/2 = 5.5 days) were stable in plasma, and were detectable in the circulation up to 3 weeks after the infusion. These findings validate primates as reliable models for Hu2G10 and Hu2EF toxicity and PK, and support the use of these antibodies as next-generation anti-Trop-2 immunotherapy tools.